EFISIENSI PENGGUNAN MODAL KERJA PADA PERUSAHAAN MEUBEL SEYLA - LCA Robin Jonathan (Universitas 17 Agustus 1945 Samarinda, 2013)
Research objectives are to: (1) measure the efficient use of working capital at a company, (2) know the amount of working capital used in a company, and (3) shows good and correct financial management.The research was conducted for 3 months at a furniture business in the company